Hypertriglyceridemia in Patients with Ischaemic Heart Disease: Hypertriglyceridemia in Ischemic Heart Disease - Khan, Muhammad Kamran; Zubair, Muhammad; Gul, Ambreen; Tariq, Muhammad; Haq, Momina; Faiz, Maria (Pakistan Journal of Health Sciences, 2024)
Cardiovascular Diseases (CVD) have been the main cause of mortality in non-communicable diseases. Managing hypertriglyceridemia is crucial for lowering the risk of cardiovascular disease. Objective: To find out the frequency of increased triglycerides in the local population of patients with ischemic heart disease. Methods: A descriptive study design was conducted from October 16, 2020, to April 15, 2021, at the Lady Reading Hospital Department of Medicine in Peshawar. A total of 182 patients were enrolled using non-probability consecutive sampling calculated by WHO sample size calculator, with ages being of 20 years and 60 years, irrespective of gender. The presence or absence of hypertriglyceridemia was stratified according to different age groups, gender, height, weight, Body Mass Index (BMI), presence/absence of hypertension, diabetes and smoking history and a level of 150 mg/dl was deemed necessary to confirm the existence of hypertriglyceridemia. Post-stratification chi- squared test was applied in which a p-value of ≤0.05 was considered significant. Results: The average age, weight, height and BMI were 50 ± 7.5 years, 75.14 ± 5.8 kg, 172.89 ± 6.4 cm and 25.204 ± 2.29 kg/m2 respectively. Patients with the history of diabetes, hypertension and smoking were 32.4%, 47.3%, and 40.1% accordingly and when comparing these parameters with hypertriglyceridemia produced highly significant results (p-value 0.001- 0.002). Conclusions: It was concluded that patients with history of smoking, hypertensions and BMI of more than 25kg/m2 are more likely to have hypertriglyceridemia, and hence more likely to be linked to cardiovascular events.